«La struttura intima del cervello creatore». La nova critica d’arte di Mariano L. Patrizi (Itinera, 2013)
The exploration of the psycho-anthropological aspect of art history was the main purpose of Mariano Luigi Patrizi, criminologist and physiologist. This paper aims to present his short biography and examine his contribution to art theory and aesthetics, focusing on his major work, Un pittore Criminale, Caravaggio e la nova critica d’arte, published in 1921.